Effect of bacillus thuringiensis on parasitoids and predators - De Bortoli, Sergio Antonio [UNESP]; Vacari, Alessandra Marieli [UNESP]; Polanczyk, Ricardo Antonio [UNESP]; Veiga, Ana Carolina Pires; Goulart, Roberto Marchi (Springer Nature, 2017)
Advances in biotechnological studies have led to the development of genetically modified (GM) crops. The commercial release of transgenic plants producing Bacillus thuringiensis (Bt) insecticidal proteins has contributed to the management of several insect pests worldwide. Additionally, the use of selective products such as Bt-bioinsecticides allows for the conservation of beneficial organisms, including parasitoids and predators, in agricultural ecosystems, thus reducing chemical insecticidal applications. The use of these bioinsecticides reduces production costs, improves product quality, and can serve as a good strategy to slow the evolution of resistance in insect pest populations. Numerous studies have investigated the effects of Bt on insect pests and on their natural enemies. Here we review the effects of Bt on parasitoids and predators and emphasize that although Bt should be selective for natural enemies, special attention should be paid to the sublethal effects of these products on the biology and/or behavior of natural enemies. Thus, this chapter describes the possible effects of Bt on some predators and parasitoids species, including Bt-bioinsecticides and GM plants.
Keywords: Bt-bioinsecticides; GM crops; Integrated pest management; Natural enemies